REASON OF DISORDERS IN THE FETOPLACENTAL BLOOD FLOW SYSTEM AND THEIR ROLE IN THE DEVELOPMENT OF FETAL GROWTH RESTRICTION SYNDROME (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The article presents the effectiveness of doppler imaging for assessing blood flow in large vessels, including the umbilical, uterine artery and middle cerebral artery. 90 women were examined in the second trimester, and 45 women showed signs of fetoplacental insufficiency, such as fetal growth restriction syndrome at 28-34 weeks. The study of utero-placental-fetal blood flow allows timely detection of early signs of a violation in the fetoplacental system and its timely correction.